β3 Tyrosine Phosphorylation in αIIbβ3 (Platelet Membrane GP IIb-IIIa) Outside-in Integrin Signaling - Phillips, David R.; Nannizzi-Alaimo, Lisa; Prasad, K. S. Srinivasa (Thrombosis and Haemostasis, 2001)
The platelet integrin αIIbβ3 not only binds fibrinogen and von Willebrand factor to mediate platelet aggregation and adhesion, it also serves as a signaling receptor. Platelet agonists such as ADP, thrombin and collagen induce “inside-out” signaling which activates the receptor function of αIIbβ3 for soluble fibrinogen. Subsequent platelet aggregation leads to “outside-in” signaling, inducing platelet aggregate stabilization and triggering a variety of functions important to platelet physiology. This review focuses on the role of β3 tyrosine phosphorylation in αIIbβ3 outside-in signaling. Tyrosine phosphorylation of β3 in platelets is a dynamic process which is initiated upon platelet aggregation and also by adhesion of platelets to immobilized fibrinogen. Tyrosine phosphorylation occurs on the β3 integrin cytoplasmic tyrosine (ICY) domain, a conserved motif found in thesubunits of several integrins. β3 ICY domain tyrosine phosphorylation induces the recruitment of two proteins to the cytoplasmic domains of αIIbβ3: the cytoskeletal protein myosin, important to clot retraction; and the signaling adapter protein Shc, important to platelet stimulation. The critical role of β3 tyrosine phosphorylation to platelet function was established by the diYF mouse, a novel strain which expresses an αIIbβ3 in which the two β3 ICY domain tyrosines have been mutated to phenylalanine. These mice are selectively impaired in outside-in αIIbβ3 signaling, with defective aggregation and clot-retraction responses in vitro, and an in vivo bleeding defect which is characterized by a pronounced tendency to rebleed. Taken together, the data suggest that the β3 tyrosine phosphorylation signaling mechanism is important to αIIbβ3 function and might be applicable to a wide variety of integrin-mediated events.
Keywords: Platelets; IIb 3 integrin; tyrosine phosphorylation; signaling mechanisms; arterial thrombosis